2015
DOI: 10.19030/ajee.v6i1.9249
|View full text |Cite
|
Sign up to set email alerts
|

An Online Tutorial Vs. Pre-Recorded Lecture For Reducing Incidents Of Plagiarism

Abstract: The current study compared an online academic integrity tutorial modified from Belter & du Pre (2009) to a pre-recorded online academic integrity lecture in reducing incidents of plagiarism among undergraduate students at a science and technology university. Participants were randomized to complete either the tutorial or the pre-recorded lecture and then completed an academic integrity quiz. We hypothesized that students who completed the tutorial would exhibit fewer incidents of plagiarism and complete th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Likewise, the quantitative results point to success with the asynchronous modality of delivering this type of learning content, as was similarly found by Greer et al (2012) and George et al (2013). The interactive activities also helped students to grasp core content, as evidenced by the improvement in posttest scores; this finding supports those reported by Bronshteyn and Baladad (2006) and Henslee et al (2015).…”
Section: Themesupporting
confidence: 78%
See 2 more Smart Citations
“…Likewise, the quantitative results point to success with the asynchronous modality of delivering this type of learning content, as was similarly found by Greer et al (2012) and George et al (2013). The interactive activities also helped students to grasp core content, as evidenced by the improvement in posttest scores; this finding supports those reported by Bronshteyn and Baladad (2006) and Henslee et al (2015).…”
Section: Themesupporting
confidence: 78%
“…The same familiarity with the web that tempts students to cheat can also be used to educate them, with institutions ubiquitously using their websites, Libguides, and online course sites to provide instruction about academic integrity (Greer et al, 2012;George et al, 2013). Some of this is practical, as online academic integrity tutorials and resources can be completed at a student's own pace (Henslee, Goldsmith, Stone, & Krueger, 2015;Jackson, 2006). Typically, these tutorials do not have to take up valuable class time and are less likely to exacerbate the stress and limited time that often lead to academic dishonesty (Ellery, 2008).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The gender of students was identified in 13 studies with 1361 women and 736 men participating. Five studies reported information about the age range of participants: 17-19 years (* Bendriss et al, 2015), 18+ years (* Henslee et al, 2015), > 24 years (97% of the sample; * Morgan andHart, 2013), 18-42 years (*Schuetze, 2004), and < 20 (43.3%), 20-24 (32.2%), and > 24 (24.5%) years (* Smedley et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed and immediate feedback was provided to facilitate learning. In five tutorials, students were required to complete short quizzes and practical activities (* Belter and Pré, 2009;*Curtis et al, 2013;*Dee and Jacob, 2012;*Henslee et al, 2015;*Kirsch and Bradley, 2012). Belter and Pré reported significantly fewer cases of plagiarism on written course assignments in the group of students who completed the tutorial compared to the group that did not, and students who did plagiarize earned significantly lower course grades.…”
Section: E-learningmentioning
confidence: 99%